P04.01 Return to work i patients with low grade glioma - Rydén, I (Neuro Oncol, 2019)
BACKGROUND: We now treat patients with low-grade gliomas (LGG) more aggressively as this prolong survival. Patients are typically in working age, but their ability to return to work (RTW) following treatment has not been studied. We aimed to study patterns of sick leave and return to work among LGG patients in Sweden. In addition, we explored predictors for RTW following LGG diagnosis. MATERIAL AND METHODS: We performed a nationwide register-based study of patients with grade II diffuse LGG. Data on adult patients aged 18–60 years with a histopathological diagnosis of LGG between 2005–2015 were obtained from the Swedish Brain Tumor Registry (n=381). A matched control sample (n=1900) was acquired from Statistics Sweden. Patients and controls were linked to the social insurance agency data for individual information on sick leave and disability compensation. Multivariable logistic regression was used in order to find predictors for RTW. RESULTS: One year prior to surgery there was no apparent difference between cases and controls with 90 % working. Among LGG patients there was a rapid increase in sick leave starting approximately six months prior to surgery, while the proportion of controls on sick leave remained constant. One year after surgery, 53 % had returned to work with 29 % working full time. Independent predictors for patients working one year after surgery were higher age (OR 0.96, 95 % CI 0.93–0.99, p <0.01) and more days absent from work prior to procedure (OR 0.91, 95 % CI 0.97-0.95, p <0.001), both negatively associated with RTW. CONCLUSIONS: In this cohort, more than half of the patients being diagnosed with LGG RTW within one year. Higher prior absence from work and higher age are risk factors for no-RTW. This study provides new information on rates of and factors influencing RTW in patients with LGG. FUNDING: This project was funded by research grant from the Swedish Research Council (2017-00944).